THE CORRELATION BETWEEN ENGLISH LANGUANGE LEARNING STRATEGIES AND THINKING STYLES INTENSITY - Mustafidatul Khasanah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: English is one of subject that compulsory in senior high school. Learning English is not easy for students’ who did not like this subject. In Indonesia, English regarded as foreign language so students can not practice English everywhere. Students need the appropriate language learning strategy and thinking styles to make them more comprehend in English. The aim of this research was to investigate the relationship between English language learning strategies and thinking styles intensity. The researcher design in this research was quantitative approach. The researcher took 30 participants from third grade students who take linguistic major in senior high schools. The questionnaire was used as instrument in this research. In analyzing the data, the researcher used SPSS version 26. The finding of this research showed that the third grade students mostly applied social strategy (M = 7.27) in language learning strategy context and legislative style as thinking styles most used by students’ (M = 8.20). The Pearson product-moment correlation analysis indicated a statistically significant correlation between language learning strategies and thinking styles at significant value .000. It indicates there is correlation between language learning strategies and thinking styles intensity. In brief, language learning strategies and thinking styles encourage students to learn English more effectively.Keywords: Language learning strategies, thinking styles